Adjuvant antibiotic‐loaded bone cement: Concerns with current use and research to make it work. Issue 2 (2nd March 2020) - Schwarz, Edward M.; McLaren, Alex C.; Sculco, Thomas P.; Brause, Barry; Bostrom, Mathias; Kates, Stephen L.; Parvizi, Javad; Alt, Volker; Arnold, William V.; Carli, Alberto; Chen, Antonia F.; Choe, Hyonmin; et al.
Abstract: Antibiotic‐loaded bone cement (ALBC) is broadly used to treat orthopaedic infections based on the rationale that high‐dose local delivery is essential to eradicate biofilm‐associated bacteria. However, ALBC formulations are empirically based on drug susceptibility from routine laboratory testing, which is known to have limited clinical relevance for biofilms. There are also dosing concerns with nonstandardized, surgeon‐directed, hand‐mixed formulations, which have unknown release kinetics. On the basis of our knowledge of in vivo biofilms, pathogen virulence, safety issues with nonstandardized ALBC formulations, and questions about the cost‐effectiveness of ALBC, there is a need to evaluate the evidence for this clinical practice. To this end, thought leaders in the field of musculoskeletal infection (MSKI) met on 1 August 2019 to review and debate published and anecdotal information, which highlighted four major concerns about current ALBC use: (a) substantial lack of level 1 evidence to demonstrate efficacy; (b) ALBC formulations become subtherapeutic following early release, which risks induction of antibiotic resistance, and exacerbated infection from microbial colonization of the carrier; (c) the absence of standardized formulation protocols, and Food and Drug Administration‐approved high‐dose ALBC products to use following resection in MSKI treatment; and (d) absence of a validated assay to determine the minimum biofilm eradication concentration to predict ALBC efficacy against patient specific micro‐organisms. Here, we describe these concerns in detail, and propose areas in need of research.